Assessing the impact of aging and blood pressure on dermal microvasculature by reactive hyperemia optical coherence tomography angiography - Michael Wang-Evers (Nature Portfolio, 2021)
Abstract Visualization and quantification of the skin microvasculature are important for studying the health of the human microcirculation. We correlated structural and pathophysiological changes of the dermal capillary-level microvasculature with age and blood pressure by using the reactive hyperemia optical coherence tomography angiography (RH-OCT-A) technique and evaluated both conventional OCT-A and the RH-OCT-A method as non-invasive imaging alternatives to histopathology. This observational pilot study acquired OCT-A and RH-OCT-A images of the dermal microvasculature of 13 young and 12 old healthy Caucasian female subjects. Two skin biopsies were collected per subject for histological analysis. The dermal microvasculature in OCT-A, RH-OCT-A, and histological images were automatically quantified and significant indications of vessel rarefaction in both old subjects and subjects with high blood pressure were observed by RH-OCT-A and histopathology. We showed that an increase in dermal microvasculature perfusion in response to reactive hyperemia was significantly lower in high blood pressure subjects compared to normal blood pressure subjects (117% vs. 229%). These results demonstrate that RH-OCT-A imaging holds functional information of the microvasculature with respect to physiological factors such as age and blood pressure that may help to monitor early disease progression and assess overall vascular health. Additionally, our results suggest that RH-OCT-A images may serve as a non-invasive alternative to histopathology for vascular analysis.